2021
DOI: 10.1007/s10854-021-05650-x
|View full text |Cite
|
Sign up to set email alerts
|

Extending the luminescence properties of zinc gallogermanate via co-doping with cost-effective metals ions (Cr3+/Mg2+, Cr3+/Ca2+, and Cr3+/Sr2+)

Abstract: The huge applications of red-light emitting materials paying the research attention to reduce the cost of production and raw materials. Therefore, abundant cations of alkaline earth metals e.g. Mg 2+ , Ca 2+ and Sr 2+ were successfully incorporated with Cr 3+ : Zn 3 Ga 2 Ge 2 O 10 (Cr-ZGGO) as co-activators via simple solidstate method. The X-ray diffraction (XRD) results of all samples con rmed the formation of zinc gallogermanate superstructure with two cubic phases ZnGa 2 O 4 and Zn 2 GeO 4 . The particle i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Another route for tuning the PersL colour is co-doping other trap or activator ions, such as Cr 3+ /Mg 2+ , Cr 3+ /Ca 2+ , Cr 3+ /Sr 2+ , and Cr 3+ /Pr 3+ co-doping. 19,20 However, as far as we know, the Cr 3+ ,Mn 2+ co-doped ZGGO phosphor with dynamic colour changes has not been reported yet. 21 Herein, we synthesize multi-mode ZGGO:Cr,Mn afterglow phosphors by a hydrothermal method combined with high temperature annealing treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Another route for tuning the PersL colour is co-doping other trap or activator ions, such as Cr 3+ /Mg 2+ , Cr 3+ /Ca 2+ , Cr 3+ /Sr 2+ , and Cr 3+ /Pr 3+ co-doping. 19,20 However, as far as we know, the Cr 3+ ,Mn 2+ co-doped ZGGO phosphor with dynamic colour changes has not been reported yet. 21 Herein, we synthesize multi-mode ZGGO:Cr,Mn afterglow phosphors by a hydrothermal method combined with high temperature annealing treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have introduced the possibility of manipulating the luminescence capabilities of PersL materials by incorporating different divalent cations that are suitable for ionic substitution. In a past study, Sanad reported an increase in luminescence intensity in Cr 3+ -doped Zn 3 Ga 2 Ge 2 O 10 when various alkaline earth metals (e.g., Mg 2+ , Ca 2+ , and Sr 2+ ) were added as dopants . The incorporation of these metal cations led to a decrease in bandgap and an overall increase in energy transfer paths, facilitating luminescence generation.…”
Section: Resultsmentioning
confidence: 96%
“…Due to the larger ionic radii of Ca 2+ relative to Zn 2+ , the successful substitution of Ca 2+ into the tetrahedral sites of CZGO would be indicated by a shift toward lower 2θ as highlighted in previous works. 53,54 However, the diffraction pattern of CZGO:Ca shows no noticeable shift. We also comparatively studied the luminescence intensity between CZGO@ACP-o, CZGO, and CZGO:Ca, which is shown in Figure S5.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation